2018
DOI: 10.1155/2018/6292308
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Sporadic Blau Syndrome with an Uncommon Clinical Course

Abstract: Background Sporadic Blau syndrome (SBS), a rare systemic inflammatory disease in children, is associated with NOD2 gene mutations. SBS is often misdiagnosed as juvenile idiopathic arthritis (JIA) because of their similar clinical manifestations. Herein, we present a case of SBS with an uncommon clinical course. Case Presentation An 11-year-old girl with recurrent right ankle swelling for 4 years was referred to our hospital. One month before admission, she developed an intermittent high fever. She was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Among the 62 patients, IFX was used in 31 patients, adalimumab in 24, and etanercept in 7. IFX was well tolerated in 27 patients [1122], while 2 patients still had uveitis [7, 23], and the other 2 experienced an adverse drug reaction to IFX infusion [21]. Adalimumab was useful in 21 BS patients [9, 14, 2328], although the other 3 patients did not get well controlled [21, 29, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 62 patients, IFX was used in 31 patients, adalimumab in 24, and etanercept in 7. IFX was well tolerated in 27 patients [1122], while 2 patients still had uveitis [7, 23], and the other 2 experienced an adverse drug reaction to IFX infusion [21]. Adalimumab was useful in 21 BS patients [9, 14, 2328], although the other 3 patients did not get well controlled [21, 29, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Rosé et al reported expended manifestations (visceral, vascular) beyond the classic clinical trial in half of the patients [ 116 ]. Physicians should consider BS as a differential diagnosis of early onset sarcoidosis in children with unusual features such as camptodactyly and normal chest computed tomography (CT), even without familial history since BS can also be sporadic [ 117 , 118 ].…”
Section: Clinical Casesmentioning
confidence: 99%
“…6 BS typically presents in early childhood with a "triad" of symptoms: granulomatous dermatitis, uveitis, and nonerosive arthritis. 2,7 However, as further cases of BS are described, novel reports of involvement of various systems have emerged. [1][2][3]5,[7][8][9][10][11] Limited reports of vascular insult exist, 8 with a total of seven available references, mainly in the form of Takayasu's arteritis.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 However, as further cases of BS are described, novel reports of involvement of various systems have emerged. [1][2][3]5,[7][8][9][10][11] Limited reports of vascular insult exist, 8 with a total of seven available references, mainly in the form of Takayasu's arteritis. 9,10 Herein, we describe a case of BS with Takayasu's arteritis lesions in an Afghan patient.…”
Section: Introductionmentioning
confidence: 99%